CLINICAL ALLERGOLOGICAL CHARACTERISTICS OF FOOD ALLERGY IN CHILDREN (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
Food allergy is a significant health concern, particularly in pediatric populations, due to its potential impact on growth, development, and quality of life. This study investigates the clinical and allergological characteristics of food allergies in children, focusing on their prevalence, clinical presentations, common allergens, and diagnostic and therapeutic approaches. The findings highlight the importance of standardized diagnostic methods and early interventions to prevent severe allergic reactions and improve patient outcomes.